Safety Challenges and Mitigation Strategies in Grid-Scale Stationary Lithium-Ion Battery Energy Storage Systems. - Afrose, Kazi Rozina (My University, 2026)
To date, Battery Energy Storage Systems (BESS) has been deployed in large-scale applications primarily to store energy in the grid, facilitate renewable energy integration, and provide grid stabilization. The BESS deployment has outpaced the development of governance mechanisms that take into account safety and environmental impacts throughout the BESS lifecycle. This thesis addresses the hazards of BESS and mitigation strategies through the combined lenses of safety and sustainability. Safety and environmental outcomes are co-produced by design, operational, and regulatory decisions, but have been historically treated in isolation. Peer-reviewed studies, inquiry investigations, standards, and life cycle assessment (LCA) studies are synthesized qualitatively. The risks of thermal runaway, fire and explosion risks, electrical hazards, and chemical contamination have been discussed in conjunction with the stages in BESS lifecycle. Thermal runaway events are life cycle environmental events and not just safety events. Emissions of hydrogen fluoride, heavy metals, and volatile organic compounds are experienced in battery fires. These emissions have often been outside the boundaries of LCA, and the resulting impacts on the environment have been underestimated. Production flaws lead to double jeopardy, increasing the loss of embodied carbon and instigating contamination at the incident phase. Present regulations are not able to account for these issues adequately. One of the most important decisions in the lifecycle is the choice of battery chemistry. This decision influences the thermal stability, material demand, emissions, and recyclability of the battery. Lithium iron phosphate (LFP) is beneficial compared to nickel-rich chemistries (NMC/NCA) if used in stationary applications. The analysis of mitigation techniques shows that there is no one-size-fits-all technology available that can address the range of hazards. Risk reduction through integrated safety design has been proven to be very effective. Trade-offs are inherent in the risk suppression methods. Toxic by-products and polluted run-offs are some of the associated trade-offs. Avoiding the build-up of gas and delay in ignition in batteries is key, since these two factors lead to severe incidents. There is very little guidance available in assessing the environment in post-incident phases. The safety standards NFPA 855, UL 9540A, and IEC 62933 have been analysed to investigate how fire safety standards can guide environmental assessment in the post-incident phase. Fire safety standards have very strong provisions on fire safety, whereas very weak accountability on the lifecycle of the batteries. A six-layered system of governance is suggested, which includes LCA disclosure, chemically sensitive procurement, post-incident analysis, and recycling mechanisms based on deployment rates.
Keywords: safety and security; emissions; lithium-ion batteries; life cycle analysis; environmental effects; fire safety; accumulators; batteries; storage; environmental risks; fi=Sähkö- ja energiatekniikka|en=Electrical Engineering and Energy Technology|; Master’s Programme in Electrical and Energy Engineering